Evaluation of glomerular filtration rate estimation equations based on serum creatinine in healthy Chinese children and adolescents: a nationwide cross-sectional study - Chao Zhang; Chen Wang; Ruohua Yan; Xiaoxia Peng; Zimo Sun (BMJ Publishing Group, 2023)
Background Several equations for glomerular filtration rate (GFR) estimation based on serum creatinine (SCr) have been proposed for children, but most were developed among patients with kidney disease. The association between SCr and GFR may be distorted by kidney dysfunction and thus not applicable to healthy children. This study aimed to evaluate the applicability of existing SCr-based GFR estimation equations in healthy Chinese children.Methods GFR estimation equations that developed in healthy children were mainly analysed, including the Flanders Metadata (FM), simple height-independent (Simple), full age spectrum (FAS) and FAS-height equations. The FM equation assumed that GFR is proportional to the ratio of height to SCr. The Simple, FAS and FAS-height equations assumed that the ratio of GFR to population mean is equal to the reciprocal ratio of SCr to population mean (denoted by Q). Estimated GFR were calculated using data of SCr, age, sex and height collected from 12 208 healthy Chinese children aged 3 months to <20 years. The performance of GFR estimation equations was evaluated by the sex and age distribution of the estimated GFR and the deviation from the measured GFR reported by other literatures.Results The FM and Simple equations performed well in their applicable age of 1 month to 14 years, but presented undesirable sex difference after adolescence. The FAS and FAS-height equations showed reasonable development trend of estimated GFR throughout childhood, and the FAS equation had higher consistency than the FAS-height equation compared with measured GFR in healthy children. The GFR estimated by the FAS equation increased with age before 2 years, and reached the adult level thereafter without important sex difference.Conclusions The FAS equation is applicable to healthy Chinese children.